A key to amphibians & reptiles of the Continental United States and Canada - Powell, Robert; Collins, Joseph T.; Hooper, Errol D. (Univ. Press of Kansas, 1998)
A dichotomous key (that is, one that gives the user only two choices at each level of morphological scrutiny), it is designed for use in college-level herpetology or vertebrate biology courses. It will be especially useful as an effective tool for teaching the principles of taxonomy and for introducing students to the systematics of amphibians and reptiles